1986
DOI: 10.1002/hep.1840060511
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 24-norlithocholic acid in the rat: Formation of hydroxyl- and carboxyl-linked glucuronides and effect on bile flow

Abstract: 24-Norlithocholic (3 alpha-hydroxy-24-nor-5 beta-cholan-23-oic) acid is the lower homologue of lithocholic acid, a potent cholestatic agent. In order to characterize its cholestatic potential and metabolic fate, 3 beta-tritiated 24-norlithocholate was infused intravenously into adult male Sprague-Dawley rats prepared with an external biliary fistula. The results demonstrate that 24-norlithocholate does not induce cholestasis in rats when administered in doses in excess of those necessary for lithocholate to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A number of monohydroxylated short-chain bile acids has been identified in the developing organism and also, but to a lesser extent, in the adult [38][39][40]. They are known to be secreted as glucuronides [41,42]. Since some short-chain bile acids are metabolically derived from steroid hormones, their analysis may be important to the understanding of hormone turnover and balance.…”
Section: Discussionmentioning
confidence: 99%
“…A number of monohydroxylated short-chain bile acids has been identified in the developing organism and also, but to a lesser extent, in the adult [38][39][40]. They are known to be secreted as glucuronides [41,42]. Since some short-chain bile acids are metabolically derived from steroid hormones, their analysis may be important to the understanding of hormone turnover and balance.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Radominska-Pyrek et al (12)(13)(14)(15) have recently reported the simultaneous formation of a new type of glucuronide conju-gate of short-chain (C 20 -C 23 ) bile acid analogs, C 24 lithocholic acid (LCA) (16), and hyodeoxycholic acid (HDCA) (17) in significant amounts by rat liver microsomal glucuronosyltransferase, together with the expected hydroxyllinked metabolites. The novel glucuronide-conjugated bile acids, termed acyl, ester, or carboxyl-linked glucuronides, have an ester linkage between the terminal carboxyl group at C-24 in the side chain of bile acids and the 1′-β-hydroxyl group in β-D-glucuronic acid.…”
mentioning
confidence: 99%
“…1 H nuclear magnetic resonance (NMR) spectra were obtained on a JEOL JNM-EX 270 FT NMR instrument (Tokyo, Japan) at 270 MHz, with CDCl 3 , CDCl 3 containing 20% dimethylsulfoxide (DMSO)d 6 or CD 3 OD containing 0.1% Me 4 Si as the solvent; chemical shifts are expressed as δ ppm relative to Me 4 Si. High-resolution mass spectra (HR-MS) were obtained on a JEOL JMS-LCmate double focusing magnetic mass spectrometer equipped with an electrospray ionization (ESI) probe under the positive ion mode (PIM) [M + Na] + for benzyl ester derivatives (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) or negative ion mode (NIM) [M − H] − for free esters (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). For reference compounds, polypropylene glycol (50 ppm) in methanol for 1 and 2, or polyethyleneglycol (50 ppm) in methanol for 3-14 was used in PIM; and sodium trifluoroacetate (200 ppm) and sodium acetate (40 ppm) in methanol for 15 and 16, or polyethyleneglycol sulfate (50 ppm) in methanol for 17-28 was used in NIM.…”
mentioning
confidence: 99%
“…Instead, these nor-bile acids are excreted as a complex mixture of biotransformation products, the majority of which are glucuronides (4). Recently, Shattuck et al (5) have shown that, in the rat, nor-LC is cholestatic and is metabolized to hydroxyland carboxyl-linked glucuronides. Nor-bile acids have been identified in the urine of healthy subjects (6) and patients with cerebrotendinous xanthomatosis (7).…”
mentioning
confidence: 99%